Contradiction and Preference According to Ibn Daqiq Al-Eid (625H - 702 AH) in his Book (Ehkam Al-Ahkam Sharh Umdat Al-Ahkam) - Mahmoud , Jabbar (Islamic Sciences Journal, 2023)
ABSTRACT Knowing the opinions of scholars, especially the people of concern among them, on various topics from the principles of jurisprudence is an important factor in many issues, including clarifying the picture of the issue, including determining the place of dispute and the subject of dispute. How many issues have been discussed in the dispute, and if the subject of the dispute is not united, or The disagreement is verbal. Including restricting issues to what some writers may release, including correcting the doctrines of scholars in what may be attributed to them of sayings they do not go to, that the narration about them is a mistake, or a mistake in understanding the words of the imams, or a remedy for transmission, or editing of a doctrine, or quoting from lost books With what the early scholars of clarity of mind, and accuracy of opinion. I am not one of those who say: The first did not leave anything to the last, but creativity is renewed every time, and for every time there is a state and men.